On the methodological problems of some works which have been studying Mongolian philosophy since the 1990s - Sukhbat, Soyolmaa (Studia Philosophiae Et Juris, 2022)
In this article, we would like to briefly consider the experience of studying Mongolian philosophy since the 1990s, and then propose some new methodological approaches. When we selected some of the works that have studied the Mongolian philosophy since the 1990s, we tried to choose the works of scientists and philosophers who have been discussed and approved by the academic council of the professional organization, are recognized by the public, or have received their doctorates. In these works, we carefully considered the experience of dealing with philosophy, and focused only on methodological issues. Since the 1990s, the experience of studying Mongolian philosophy through historical-comparative methods has been predominant. Also, there is a common tendency that most of the research scientists considered Mongolian philosophy only in terms of socio-political relations or in the context of Buddhist religion. In the result of discussion, we came to a conclusion that it is important to study Mongolian philosophy in the sense that it is a creative finding, discovers the meaning of concepts, modernizes, solves philosophical fundamental problems, and opens new concepts. When studying Mongolian philosophy, it is advisable to adopt a humanistic and cultural position and combine the methodology with the characteristics of philosophical methods such as phenomenology, hermeneutics, structure-symbolism, and historical comparison. Монголын философийг 1990 –ээд оноос хойш судалж ирсэн зарим бүтээлийн арга зүйн асуудалд Энэ өгүүлэлд бид Монголын философийг судалсан 1990-ээд оноос хойших судалгаа шинжилгээний зарим бүтээлүүдийн арга зүйг товч авч үзээд улмаар философийн шинэлэг арга зүйн хандлагыг санал болгохыг зорьсон юм. Бид мэргэжлийн байгууллагын эрдмийн зөвлөлөөр хэлэлцүүлж батлуулсан, олон нийтэд хүлээн зөвшөөрөгдсөн, докторын зэрэг хамгаалсан эрдэмтэн, философичдын бүтээлийг сонгон авч хэлэлцэхийг хичээсэн юм. Эдгээр бүтээлүүдийн Монголын философи, ерөөс философи хэмээх ойлголтыг хэрхэн авч үзсэнийг хэлэлцэж, зөвхөн арга зүйн судалгаанд анхаарлаа хандуулсан. 1990-ээд оноос хойш Монголын философийг түүхэн[1]харьцуулалтын аргаар судлах туршлага зонхилж байна. Мөн судлаач эрдэмтэдийн дийлэнх нь Монголын философийг нийгэм-улс төрийн харилцаанд (нийгмийн бүлэг хоорондын харилцааны утгаар биш) эсвэл Буддын шашны хүрээнд авч үзсэн нийтлэг хандлага байна. Хэлэлцүүлгийн үр дүнд Монголын философийг бүтээлч, ойлголтын утгыг нээдэг, асуудал шийддэг, шинэ ухагдахуун нээдэг гэдэг утгаар нь судлах нь чухал, мөн Монголын философийг судлахад хүмүүнлэг, соёлын байр суурийг баримталж, феноменологи, герменевтик, бүтэц тэмдэг зүйн болон түүхэн харьцуулалтын гэх мэт философийн онцлог бүхий арга зүйг хослуулах нь зүйтэй юм гэсэн дүгнэлтэд хүрсэн юм. Tүлхүүр үгс: Монгол, философи, түүх, логик, бүтэц, ойлголт, утга, арга, бүтээл, үйл явц